External fixation of the lower extremities: Biomechanical perspective and recent innovations. (June 2019) - Bliven, Emily K.; Greinwald, Markus; Hackl, Simon; Augat, Peter
Highlights: Short historical overview of external fixation principles. Biomechanical advances in construct configurations. Innovative and rediscovered practical application of external fixation. External fixation in the age of IoT (Internet of Things). Abstract: The concept of supporting fractured long bones externally with mechanical fixation has been evidentially applied for over 2000 years, and since been expanded on in the mid-19th century by percutaneous bone fixation. Surgical techniques, external fixator systems, and materials have made continued progress since. The benefits of traditional external fixation have been enhanced in recent years with the introduction of hexapod-style fixators, innovative configurations, and pin modifications, among other things. It is generally agreed upon that biomechanical testing of advancements in external fixation must be inclusive of transverse or torsional loading to simulate construct behaviour in realistic scenarios. Biomechanical studies indicate that hexapod-style fixators show comparable axial stiffness to Ilizarov-style systems and improved performance under torsional and transverse forces. The addition of configuration elements to fixators, inclusion of certain carbon fibre chemical compositions, and techniques intended to augment ring thickness have also been investigated, in hopes of increasing construct stiffness under loading. Novel external fixators attempt to broaden their applications by rethinking bone mounting mechanisms and either expanding on or simplifying the implementation of 3D bone segment transport for corrective osteotomy. Older and seemingly unconventional fixation techniques are being rediscovered and evolved further in order to increase patient comfort by improving everyday usability. The development of new pin coatings can potentially enhance the pin-bone interface while lowering infection rates typically expected at thicker soft tissue envelopes. Although complication, malunion, and nonunion rates have decreased over the past 50 years, the clinical results of external fixation today can still be optimized. Unsatisfactory healing in the lower extremities has especially been reported at locations such as the distal tibia; however, advancements such as osteoinductive growth hormone treatment may provide improved results. With the current progression of technology and digitization, it is only a matter of time before 'smart', partly-autonomous external fixation systems enter the market. This review article will provide a versatile overview of biomechanically proven fixator configurations and some carefully selected innovative systems and techniques that have emerged or been established in the past two decades.